I Feel it Coming? Exploring the Relation Between Personality Traits, Expectations, and Precognition in a Forced-Choice Experiment - Helmius,Maria; Sundh,Joakim (2025)
This thesis aimed to explore the relation between openness to experience, extraversion, belief in succeeding in a precognitive task, and precognition, measured with the forced-choice precognitive task the Selfield. Sixty participants were recruited and completed a total of 2,381 trials. Personality traits were measured using the Swedish version of the Big Five Inventory (BFI) and belief in succeeding in the task was measured using a single item. In contrast to previous research, we found a small to moderate negative correlation (r = - .29 to -.33, p = <.05) between openness to experience and precognition. Correlations between belief in succeeding in the task, extraversion, and precognition were non-significant. A binomial test showed that our sample as a whole did not perform significantly better than chance level, thus failing to support the existence of precognition. The surprising negative relation between openness to experience and precognition challenges previous research and may reflect random variation, methodological restrictions, or more complex underlying mechanisms. The discussion explores potential explanations such as experimenter effects, limitations in construct validity, and challenges with the elusiveness of psi phenomena. Despite limitations, the study contributes to the methodological advancement of psi research. By integrating psychological variables with Selfield task, it opens new perspectives for exploring individual differences in relation to precognition. Further research using more robust measures and larger samples is necessary to replicate and build upon these findings.
Keywords: Parapsychology; Precognition; Personality Traits; Parapsykologi; prekognition; personlighetsdrag